2018
DOI: 10.3390/plasma1010018
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Treatment of Ovarian Cancer Cells Mitigates Their Immuno-Modulatory Products Active on THP-1 Monocytes

Abstract: Cancers modulate their microenvironment to favor their growth. In particular, monocytes and macrophages are targeted by immuno-modulatory molecules installed by adjacent tumor cells such as ovarian carcinomas. Cold physical plasma has recently gained attention as innovative tumor therapy. We confirmed this for the OVCAR-3 and SKOV-3 ovarian cancer cell lines in a caspase 3/7 independent and dependent manner, respectively. To elaborate whether plasma exposure interferes with their immunomodulatory properties, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Several studies by others and us have observed plasma-induced tumor cell death before [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Kumar and colleagues observed in several pancreatic cancer cell lines an increase in apoptosis concomitant with downregulation of MAPK7, BCL2, and CHK1 [99].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies by others and us have observed plasma-induced tumor cell death before [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Kumar and colleagues observed in several pancreatic cancer cell lines an increase in apoptosis concomitant with downregulation of MAPK7, BCL2, and CHK1 [99].…”
Section: Discussionmentioning
confidence: 94%
“…These signals can be transmitted using soluble molecules, communication junctions (ion channels, pannexins, gap junctions and chemical synapses), occluding junctions (tight junctions) and anchoring junctions (adherens, desmosomes, focal adhesions, and hemidesmosomes) ( Table 2). The expression of soluble cues, such as chemokines, cytokines, and growth factors, are directly affected by the oxidative stress induced by plasma, as demonstrated before in cancer and immune cells [134,194,195]. In particular, tumour cells exposed to plasma or plasma-treated medium can induce a bystander effect that leads to cell death in the untreated neighbouring population, a process mediated by the generation of secondary 1 O 2 and inactivation of membrane-bound catalase, as discussed in Section 2 [60,97].…”
Section: Cell-to-cell Communicationmentioning
confidence: 71%
“…The messages sent between cells can also be transmitted via tunnelling nanotubes and extracellular vesicles (EVs) that allow cargo exchange between cells located at short or long distances. Interestingly, plasma was able to hinder the formation of extracellular vesicles produced by ovarian cancer cells [195], which cargoes could stimulate pro-oncogenic responses and therapy resistance in neighbouring cancer cells. This is particularly important in the TME, as the crosstalk between malignant and stromal cells participates in the regulation of proliferation, angiogenesis, evasion of cells of the immune system and cell recruitment.…”
Section: Cell-to-cell Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The second part of the book is a collection of 8 papers published in the special issue on plasma medicine. The first paper is an introductory review of the field of plasma medicine [52]; some of the following papers discuss the applications of various plasma jets for cancer treatment, including triple-negative breast cancer cells, ovarian cancer cells, and the manner in which plasma can decrease the viability of malignant solid tumors cells [53][54][55]. One paper presents a performance evaluation of three plasma sources/jets [56], while two other papers discuss how plasma modulates the responsiveness of human macrophages and cellular glucose uptake [57,58].…”
mentioning
confidence: 99%